PENGARUH KEPEMIMPINAN, MOTIVASI DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA - Sulistianto, 08.05.51.0039; Utomo, Budi Sungkowo (Students Journal of Economic and Management, 2012)
An organization / company will function effectively if handled by people who have skills and high work productivity in performing the tasks assigned to him. Value is the value added of activities of the people there, and the value thus also referred to as an increase in labor productivity. Some of the factors that affect work productivity is leadership, motivation and training. The purpose of this study was to analyze the effect of leadership, motivation and training on employee productivity. Sample collection technique is the technique of non-random (non random / non-probability) and census techniques. Is the primary data type. Methods of data collection using questionnaires. The analysis technique used is multiple regression. The results of the analysis using SPSS Version 13 show that: (1). Leadership has positive and significant impact on labor productivity. (2). Motivation has positive and significant impact on labor productivity. (3). Training has positive and significant impact on laborproductivity. Key words: Leadership, Motivation, Training and Employee Productivity